Reproduction of an azooxanthellate coral is unaffected by ocean acidification. Issue 1 (December 2017) - Gizzi, Francesca; de Mas, Ludovica; Airi, Valentina; Caroselli, Erik; Prada, Fiorella; Falini, Giuseppe; Dubinsky, Zvy; Goffredo, Stefano
Abstract Anthropogenic carbon dioxide (CO2 ) emissions and consequent ocean acidification (OA) are projected to have extensive consequences on marine calcifying organisms, including corals. While the effects of OA on coral calcification are well documented, the response of reproduction is still poorly understood since no information are reported for temperate corals. Here we investigate for the first time the influence of OA on sexual reproduction of the temperate azooxanthellate solitary scleractinianLeptopsammia pruvoti transplanted along a naturalp CO2 gradient at a Mediterranean CO2 vent. After 3 months, future projection of pH levels did not influence the germ cell production, gametogenesis and embryogenesis in this azooxanthellate coral. These findings suggest that reproductive potential may be quite tolerant to decreasing pH, with implications for ecosystem function and services in a changing ocean.